ANALYSIS OF PHYSIOLOGICAL AND MORPHO-AGRONOMIC TRAITS OF UPLAND COTTON UNDER DIFFERENT CONDITIONS OF WATER SUPPLY - Hilola Matniyazova; Saydigani Nabiyev; Gulrukhsor Ergasheva; Nodira Mamadaliyeva (The Bioscan, 2024)
Accordingato theaauthors, uplandacotton linesaadapted to wateradeficit byachangingathe total wateracontent andatranspiration rateain thealeavesaof theaplants, withavaryingadegreaseaand varyingadegrees ofaincrease inawater retentionain thealeaves. Itawas foundathat theatraitaof transpirationarate isathe mostainfluential signaof wateradeficiency amongathe studiedatraits. It was found that the content of chlorophyll a, chlorophyll b and carotenoids in leaves of upland cotton line plants decreases in different degrees in water deficit compared to optimal water supply. The amount of proline amino acid was found to increase in different degrees. Plant productivity was reduced in upland cotton lines under water deficit compared to control (optimal water regime). Relatively high productivity and durability under these stress conditions were recorded in L-22, L-11, L-15 and L-7 lines. Itawasafoundathatathe water retention capacity of leaves degreases with the increase of transpiration rateain theaupland cotton lines against the condition of different water supply. It was found that there is a positive correlation between the increase in the water retention property of leaves and the increase in plant productivity in water deficit condition.